AEROBIC EXERCISE INCREASE FUNCTIONAL CAPACITY ON POST ATRIAL SEPTAL DEFECT CLOSURE PATIENT: A CASE STUDY - Martani, Laras Rum; Supriyadi, Arin (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Atrial Septal Defect (ASD) are common and present at any age. Atrial septal defect (ASD) is a congenital heart defect that enables blood flow between the left and right atria through a defect in the interatrial septum. ASDs compose 35% to 40% of congenital heart defects, making them the second most common congenital heart defect. The ratio of ASD sufferers is 1:2 male to female. Treatment options are determined based on time of discovery and size and location of defect. Surgical correction is ideal before pulmonary hypertension develops, and has the lowest risk of complications when performed in patients<25y, closure may be performed as open heart surgery. Case Presentation:A female 26 years old with a diagnosis of ASD. Patient complained fatigue, and dyspnea. Echocardiographic before operation showed ASD secundum 20 mm left to right shunt, diastolic dysfunction grade 1 and ejection friction 78.1% probability pulmonary hypertension. Management and Outcome:An aerobic exercise were used in this study. The program performed 3 sessions in a week during 4 weeks. The 6-minutes walking test were used to evaluate functional capacity. Discussion:After giving an aerobic exercise during 1 month obtained the result increase functional capacity. Patients was able to walk as far as 220 meters in 6 minutes. Conclusion: : Physiotherapy management in post ASD closure phase II for 12 sessions of aerobic exercise program showed a good progression.